Prospects of Training & Development in Tourism Sector: The Current Scenario - Garg, Shalini (Journal of Commerce and Trade, 2007)
Tourism is the world’s largest and fastest growing industry. It is also the biggest in terms of employment. Commonly associated with ‘fun’, tourism is a major industry in its own right. It is probably unmatched in terms of the diversity of the sectors it embraces such as hotels, travel agencies, airlines, restaurants, shops, resorts, conventions and so no. In fact, its very diversity of sectors underscores the intrinsic uniqueness of the industry – the multi – component nature of the visitor experience. Developing tourism as an industry is thus critical, and an effective and far reaching industrial strategy is required. The present paper is an effort in this direction, which stress upon the role of training & development in fostering professionalism in the business of travel and tourism.